COVID-19 and Heart Failure: From Epidemiology During the Pandemic to Myocardial Injury, Myocarditis, and Heart Failure Sequelae - Italia, Leonardo; Tomasoni, Daniela; Bisegna, Stefano; Pancaldi, Edoardo; Stretti, Lorenzo; Adamo, Marianna; Metra, Marco (Frontiers in Cardiovascular Medicine, 2021)
A close and intriguing relationship has been suggested between heart failure (HF) and coronavirus disease 2019 (COVID-19). First, COVID-19 pandemic represented a global public health emergency in the last year and had a catastrophic impact on health systems worldwide. Several studies showed a reduction in HF hospitalizations, ranging from 30 to 66% in different countries and leading to a subsequent increase in HF mortality. Second, pre-existing HF is a risk factor for a more severe clinical course of COVID-19 and an independent predictor of in-hospital mortality. Third, patients hospitalized for COVID-19 may develop both an acute decompensation of chronic HF and de-novo HF as a consequence of myocardial injury and cardiovascular (CV) complications. Myocardial injury occurred in at least 10% of unselected COVID-19 cases and up to 41% in critically ill patients or in those with concomitant CV comorbidities. Few cases of COVID-19-related acute myocarditis, presenting with severe reduction in the left ventricular (LV) ejection fraction and peculiar histopathological findings, were described. However, recent data suggested that COVID-19 may be associated with both systolic and diastolic LV dysfunction, with LV diastolic impairment, pulmonary hypertension, and right ventricular dysfunction representing the most frequent findings in echocardiographic studies. An overview of available data and the potential mechanisms behind myocardial injury, possibly leading to HF, will be presented in this review. Beyond the acute phase, HF as a possible long-term consequence of cardiac involvement in COVID-19 patients has been supposed and need to be investigated yet.